Nippur. I. Temple of Enlil, Scribal Quarter, and Soundings. Exeavations of the Joint Expedition to Nippur of the University Museum of Philadelphia and the Oriental Institute of the University of Chicago. - McCown, D. E. (1967)
By Donald E. McCown and Richard C. Haines, assisted by Donald P. Hansen; 133s.